The power of sports tradition and its influence on long-standing engagement of athletes in running races - Miloš Bednář (Karolinum Press, 2019)
Analysis of the general role of tradition formed wider theoretical background of the paper. We used hermeneutic analysis to interpret this role. We attempled to formulate own definition of tradition using the term of social time. Well-known world competitions served as an example of power of tradition in the field of sport. Special attention was paid to the Olympic movement and two parallel but different inspirations from the heritage of the ancient Olympism in the case of the Sokol sports and social movement and the Modern Olympics. In a longitudinal study we researched a group of runners who participated repeatedly in the 10K Czech race "Běchovice - Praha". It was founded in 1897 and has been held each consecutive year. Our aim was to illustrate how the tradition of one race can engage runners in lifelong physical activities. We found 322 runners who participated 20 times and more. Constancy of the route, non-stop organizing, engagement of the whole families, celebrations of anniversaries, and wider publicity were found to be factors in building loyalty to the race. We discussed some aspects of comparison with similar studies as well. Particular attention was paid to the Boston Marathon and especially to means of supporting loyalty of runners.